RETRACTED: The Design, Characterizations, and Tumor Angiogenesis Inhibition of a Multi-Epitope Peptibody With bFGF/VEGFA - Zhang, Ligang; Deng, Yanrui; Zhang, Yinmei; Liu, Chunyan; Zhang, Simin; Zhu, Wenhui; Tang, Yong; Deng, Ning (Frontiers in Oncology, 2020)
Tumor angiogenesis is growth factors dependent and inhibition of their pathways is one of the promising strategies in cancer therapy. However, resistance to single pathway has been a great concern in clinical trials so that it necessitates multiple targetable factors for developing tumor angiogenesis inhibitor. Moreover, the strategy of Fc fusion protein is an attractive platform for novel peptide agents, which gains increasing importance with FDA approval because of better immunogenicity and stability. Here we applied Fc fusion protein concept to bFGF/VEGFA pathways and designed a multi-epitope Peptibody with immunogenic peptides derived from human bFGF and VEGFA sequences. Immunization with Peptibody could elicit high-titer anti-bFGF and anti-VEGFA antibodies, activate T cells and induce Th1/Th2 type cytokines. In vitro experiments, the isolated anti-Peptibody antibody inhibited the proliferation and migration of A549 cells and HEVECs by decreasing the MAPK/Akt/mTOR signal pathways. In murine tumor model, pre-immunization with Peptibody suppressed the tumor growth and neovascularization of lung cancer by decreasing the production of bFGF/VEGFA/PDGF, the MAPK/Akt/mTOR signal pathways and the activation of suppressive cells in tumor sites. Further, the biological characterizations of the recombinant Peptibody were investigated systematically, including protein primary structure, secondary structure, stability and toxicity. Collectively, the results highlighted the strategy of bFGF/VEGFA pathways and Fc fusion protein in suppressing tumor progression and angiogenesis, which emphasized the potential of multiple targetable factors for producing enduring clinical responses in tumor patients.